Folate-Targeted Nanoliposomal Chemophototherapy - Upendra Chitgupi; Yiru Qin; Sanjana Ghosh; Breandan Quinn; Kevin Carter; Xuedan He; Ulas Sunar; Jonathan F. Lovell (MDPI AG, 2023)
Light-responsive liposomes have been developed for the on-demand release of drugs. However, efficient delivery of chemotherapeutic drugs to tumor for cancer theranostics remains a challenge. Herein, folic acid (FA), an established ligand for targeted drug delivery, was used to decorate light-sensitive porphyrin-phospholipid (PoP) liposomes, which were assessed for FA-targeted chemophototherapy (CPT). PoP liposomes and FA-conjugated PoP liposomes were loaded with Doxorubicin (Dox), and physical properties were characterized. In vitro, FA-PoP liposomes that were incubated with FA receptor-overexpressing human KB cancer cells showed increased uptake compared to non-targeted PoP liposomes. Dox and PoP contributed towards chemophototherapy (CPT) in vitro, and PoP and FA-PoP liposomes induced cell killing. In vivo, mice bearing subcutaneous KB tumors treated with PoP or FA-PoP liposomes loaded with Dox, followed by 665 nm laser treatment, had delayed tumor growth and improved survival. Dox delivery to tumors increased following laser irradiation for both PoP and FA-PoP liposomes. Thus, while Dox-FA-PoP liposomes were effective following systemic administration and local light irradiation in this tumor model, the FA targeting moiety did not appear essential for anti-tumor responses.